TAX INCENTIVES AND FEDERATIVE CONFLICT IN BRAZIL: HOW THE TAX SYSTEM AFFECTS COOPERATION AMONG STATES (REMUNOM, 2026)
This article analyzes tax incentives in Brazil from the perspective of federal conflict, highlighting how the tax system influences state cooperation. Initially, the theoretical foundations of Brazilian fiscal federalism and the historical evolution of tax incentives are presented, emphasizing the challenges imposed by tax decentralization. The phenomenon of fiscal competition is discussed in depth, identifying its impacts on federal cooperation, such as the intensification of regional inequalities and the erosion of state public revenues. Emblematic cases, such as the Manaus Free Trade Zone, illustrate the dilemmas associated with granting tax benefits. The article also addresses regulatory measures and tax reform proposals, analyzing initiatives such as Complementary Law No. 160/2017 and the creation of the Goods and Services Tax (IBS). Finally, reflections are made on the need to modernize tax governance, strengthen transparency, and align tax incentives with long-term goals, such as technological innovation and environmental sustainability. It concludes that the construction of a more integrated and cooperative model is essential to transform tax incentives into effective instruments for national development and federal balance.